2006
DOI: 10.1111/j.1460-9568.2006.04890.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of GABAAβ2 subunit‐containing receptors in mediating the anticonvulsant and sedative effects of loreclezole

Abstract: The majority of inhibitory neurotransmission in the brain is mediated by the gamma-aminobutyric acid (GABA) type A (GABA(A)) receptor. The anticonvulsant loreclezole largely acts by potentiating GABA(A) receptors containing beta2 and beta3 subunits. We used a genetically modified mouse containing a loreclezole-insensitive beta2 subunit (beta2N265S) to determine the role of this subunit in mediating the sedative and anticonvulsive effects of loreclezole. Sedation was assessed by measuring spontaneous locomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…This finding is similar to that reported for knock-in mice possessing a loreclezoleinsensitive GABA A β2 receptor (Groves et al, 2006). As observed here in Fmr1 knockout mice, the loreclezole-insensitive β2 receptor mice showed less loreclezole-induced sedation, as measured by spontaneous motor activity, compared to wild-type mice.…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micesupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is similar to that reported for knock-in mice possessing a loreclezoleinsensitive GABA A β2 receptor (Groves et al, 2006). As observed here in Fmr1 knockout mice, the loreclezole-insensitive β2 receptor mice showed less loreclezole-induced sedation, as measured by spontaneous motor activity, compared to wild-type mice.…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micesupporting
confidence: 91%
“…A previous study demonstrated that mutant knock-in mice containing a loreclezole-insensitive β2 subunit were significantly less protected from pentylenetetrazole-induced seizures when treated with loreclezole (Groves et al, 2006 (Pacey et al, 2009). Increased susceptibility to audiogenic seizures in knockout mice may depend more on changes in group I mGluRs (Giuffrida et al, 2005) and GABA B receptor-mediated signalling than on GABA A receptor activity.…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the ␤2/␤3 selective agent loreclezole has sedative properties. 197,198 Substantial effort has been devoted to obtaining GABA A receptor positive allosteric modulators that have reduced activity on GABA receptors containing ␣1 subunits, to avoid the sedation that is believed to be mediated by these receptors. The compounds developed so far are generally nonbenzodiazepines that bind to the benzodiazepine site on all benzodiazepine-sensitive isoforms, but at certain isoforms are partial agonists with reduced efficacy.…”
Section: Cys-loop Ligand-gated Channelsmentioning
confidence: 99%